2020
DOI: 10.1002/eap.2142
|View full text |Cite
|
Sign up to set email alerts
|

Dry conifer forest restoration benefits Colorado Front Range avian communities

Abstract: Fire suppression has increased stand density and risk of severe, stand‐replacing wildfire in lower elevation dry conifer forests of western North America, threatening ecological function. The U.S. Forest Service’s Collaborative Forest Landscape Restoration Program (CFLRP) aims to mitigate impacts to ecological function, while mandating effectiveness monitoring to verify restoration success. Expected benefits include improved conditions for biodiversity, but relatively few empirical studies evaluate restoration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…If the objective with growing the Norway spruce stand together with admixture of broadleaves is to increase nature conservation values, then this issue needs to be considered from the outset of the thinning regime. Simulations of thinning approach in mixtures demonstrate positive effects of maintaining clustering tree structures for maintained or increasing within-stand heterogeneity (Cannon et al 2019) as well as a general increase of species richness with increasing forest heterogeneity (Felton et al 2016;Latif et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If the objective with growing the Norway spruce stand together with admixture of broadleaves is to increase nature conservation values, then this issue needs to be considered from the outset of the thinning regime. Simulations of thinning approach in mixtures demonstrate positive effects of maintaining clustering tree structures for maintained or increasing within-stand heterogeneity (Cannon et al 2019) as well as a general increase of species richness with increasing forest heterogeneity (Felton et al 2016;Latif et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, avian diversity in the region has been found to increase with characteristics such as canopy gaps, open forest, and with spatial complexity of forest openings (Latif et al. 2020). In our study, each of these metrics was increased to a greater extent in low‐ and moderate‐severity wildfires relative to mechanical thinning treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical thinning treatments had lower average gap size, and lower gap size variability, indicating that dispersal may be less limited than following wildfires and showing that future forest dynamics and spatial patterns may continue to diverge among these disturbance types. Moreover, avian diversity in the region has been found to increase with characteristics such as canopy gaps, open forest, and with spatial complexity of forest openings (Latif et al 2020). In our study, each of these metrics was increased to a greater extent in low-and moderate-severity wildfires relative to mechanical thinning treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, forest treatments that benefit Northern Goshawk (Accipiter gentilis) emphasize interspersion of closed canopy forests with open herbaceous areas, and the retention of older tree groups, to benefit the various organisms in the goshawk's food web (Reynolds et al 2013). Such benefits may apply more broadly to avian communities as Latif et al (2020) found that avian richness increased with measurements of forest complexity like the perimeter-to-area ratio of open forests. To evaluate the effects of each conservation approach on landscape-scale forest complexity, we quantified changes in canopy cover, large gap cover, landscape complexity, and contagion index from the canopy cover layers resulting from each treatment simulation using the raster package in R (Hijmans and van Etten 2016).…”
Section: Restoration Simulation (Restsim) Algorithmmentioning
confidence: 99%